2006
DOI: 10.4161/cbt.5.6.2674
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of hepatitis C virus-related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is triggered by many factors including infection with hepatitis C virus (HCV). However, the molecular basis of the development of HCV-related HCC remains unknown. The present study was designed to reveal the interference of the HCV infection in HCC patients with a set of anti-apoptotic factors, and expression levels of some molecular markers between HCV-related HCC and non-HCV-related HCC. We have determined the plasma circulating levels of Bcl-2, TGF-betaI, VEGF, beta2-MG and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…It suggests that bcl-2 may have a role in development or progression of HCC in patients with chronic hepatitis C. It was not correlated with total viremia or AFP or ALT levels in all patient groups either infected with HCV or not. Our data indicated that total viremia is related to AFP and bilirubin serum level in patients with chronic hepatitis C. This finding correlates with the previous reports (Sultan et al, 2006) which stated that high viral load associated frequently with HCC in patients with HCV. A study by Sultan.…”
Section: Discussionsupporting
confidence: 92%
“…It suggests that bcl-2 may have a role in development or progression of HCC in patients with chronic hepatitis C. It was not correlated with total viremia or AFP or ALT levels in all patient groups either infected with HCV or not. Our data indicated that total viremia is related to AFP and bilirubin serum level in patients with chronic hepatitis C. This finding correlates with the previous reports (Sultan et al, 2006) which stated that high viral load associated frequently with HCC in patients with HCV. A study by Sultan.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, the conventional treatments for HCC, such as liver transplantation or resection [ 7 ], radiotherapy, and chemotherapy, have severe side effects. As drug resistance and adverse effects remain two critical hurdles [ 8 ], the necessity of beefing up the development of new anticancer agents has become apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Also, caspase‐7 has been found to be activated during HSV‐1, SARS‐CoV‐2, influenza and HCV mediated infections, thereby resulting in apoptosis 24–27 . Serum Bcl‐2 level was not significantly altered in any group of dengue patients of this study, which was also noted among HCV‐infected Chinese hamster ovary (CHO‐K1) cells and sera of HCV‐infected Egyptian patients 28,29 . However, earlier studies on febrile children < 24 months age, infected with common cold causing rhinovirus and respiratory syncytial virus also exhibited increased caspase 3/7 activity 30,31 …”
Section: Discussionmentioning
confidence: 52%
“…[24][25][26][27] Serum Bcl-2 level was not significantly altered in any group of dengue patients of this study, which was also noted among HCV-infected Chinese hamster ovary (CHO-K1) cells and sera of HCV-infected Egyptian patients. 28,29 However, earlier studies on febrile children < 24 months age, infected with common cold causing rhinovirus and respiratory syncytial virus also exhibited increased caspase 3/7 activity. 30,31 Significant increase in serum level of hepatic proteins (bilirubin, AST, ALT, and ALP) among SD patients indicated correlation of…”
Section: Discussionmentioning
confidence: 92%